2022
DOI: 10.1186/s13690-022-00789-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and factors associated with adolescent pregnancy in Nigeria: a multi-level analysis

Abstract: Background Adolescent pregnancy is a global public health and social phenomenon. However, the prevalence of adolescent pregnancy varies between and within countries. This study, therefore, sought to investigate the spatial distribution and factors associated with adolescent pregnancy in Nigeria. Methods Using data from the women’s recode file, a sample of 9448 adolescents aged 15-19 were considered as the sample size for this study. We employed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…This practice increases teenage girls' chances of becoming pregnant in their late teens, and is prevalent within some ethnic groups in Nigeria especially in the northern geopolitical zones [12,13,21]. A recent study on the spatial distribution of adolescent pregnancy in Nigeria using the 2018 NDHS showed that the northern part of Nigeria had a higher proportion of adolescent pregnancy, due to higher levels of poverty and early marriage as well as lower levels of education [33].…”
Section: Discussionmentioning
confidence: 99%
“…This practice increases teenage girls' chances of becoming pregnant in their late teens, and is prevalent within some ethnic groups in Nigeria especially in the northern geopolitical zones [12,13,21]. A recent study on the spatial distribution of adolescent pregnancy in Nigeria using the 2018 NDHS showed that the northern part of Nigeria had a higher proportion of adolescent pregnancy, due to higher levels of poverty and early marriage as well as lower levels of education [33].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 21 million teenage girls aged 15–19 years become pregnant each year and the prevalence of teenage pregnancies is 95% higher in low- and middle-income countries (LMICs) compared with high-income countries [ 1 ]. Globally teenage pregnancy poses a profound public health concern [ 2 – 5 ]. For instance, pregnancy and childbirth complications are the major cause of death in teenage girls and 99% of all teenage maternal death occurs in LMICs [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of teenage pregnancy rate (106 adolescent births per 1000 population) is a major concern for the government and other stakeholders [ 2 ]. To reduce the unintended pregnancies among schoolchildren, a curriculum for sex education was introduced in Nigerian schools in 2002 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPV could have devastating effects on the physical and mental health of victims. For instance, IPV affects the reproductive health of women, which may lead to an increase in their likelihood of having miscarriages, pregnancy termination, stillbirths, induced abortions, unplanned pregnancies, and pregnancy-related complications [ 6 , 8 11 ]. Aside from the instant or short-term traumatic consequences, IPV can result in chronic health problems such as physical disability, drug and alcohol abuse and addiction, depression, suicidal ideation, and even death [ 4 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%